2011
DOI: 10.1007/s11676-011-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics associated with leaf litter decomposition of three agroforestry tree species (Azadirachta indica, Dalbergia sissoo, and Melia azedarach) of Bangladesh

Abstract: Azadirachta indica A. Juss, Dalbergia sissoo Roxb., and Melia azedarach L. are little studied species in nutrient return capabilities from leaf litter decomposition to maintenance of the soil fertility despite their importance in agroforestry practices of Bangladesh. A leaf litter decomposition experiment was conducted using a litterbag technique to assess the nutrient return efficiency of these species. The decomposition rate of leaf litter was highest for M. azedarach and lowest for D. sissoo. Rainfall and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 42 publications
(38 reference statements)
3
40
0
2
Order By: Relevance
“…Similar to our results, Singh et al (1989) and Lodhiyal & Lodhiyal (1997) reported the returned nutrient content by leaf litter in the order of N>K>P in Populus deltoides plantations in moist plain area in the north of India. However, Mahmood et al (2009Mahmood et al ( , 2011 reported nutrient release from leaf litter of three tree species in Bangladesh follows the order of K>N>P.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Singh et al (1989) and Lodhiyal & Lodhiyal (1997) reported the returned nutrient content by leaf litter in the order of N>K>P in Populus deltoides plantations in moist plain area in the north of India. However, Mahmood et al (2009Mahmood et al ( , 2011 reported nutrient release from leaf litter of three tree species in Bangladesh follows the order of K>N>P.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of nutrient and organic matter content in soils is a serious threat for agricultural production and food security in many tropical countries (Hossain et al, 2011). In this sense, agroforestry provides a sustainable opportunity to counteract this threat due to its potential to reestablish degraded or marginal soils.…”
Section: Introductionmentioning
confidence: 99%
“…Agroforestry promotes more efficient cycling of nutrients than traditional agriculture systems. It is also more sustainable and better for the environment [5][6][7]. A wide variety of horticultural tree species are used in different croplands and/or forms of agroforestry in Bangladesh [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Litter improves soil quality through adding the organic matter and nutrients to the soil [15][16][17]. Leaf litter is the main and fastest source of organic matter and nutrient to the soil compared to other litter types [6,18,19]. The nutrients in litter were added to the soil through microbial decomposition and physical leaching of soluble components followed by microbial oxidation of refractory components [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%